Decoding Politeness: A Sociolinguistic Analysis of Power and Relationships in Paulo Coelho’s Novel “The Alchemist” - Almeera Aimen; Usama Khadim; Mubeen Akbar; Dr. Jahanzeb Jahan (Dialogue Social Science Review (DSSR), 2025)
This research delves into the artful interplay between language and civility of main characters from Paulo Coelho’s novel ‘The Alchemist’, uncovering the politeness strategies that breathe life into its characters. Through a detailed examination of these dialogues, the research reveals that interpersonal dynamic and situational settings affect the language strategies. A descriptive qualitative methodology has been adopted, with data collected through careful documentation and meticulous observation of the text. The findings indicate that the characters predominantly use four main types of politeness strategies. Out of all these strategies, positive politeness emerges as the most frequently employed strategy, evident in most of the utterances used by characters of the novel. Following this comes the least common strategy of politeness, negative politeness which emphasizes the respect and acknowledges the social distance. Then off-record and bald-on-record politeness appears, but their usage is mostly context-dependent and creates a sense of urgency and informality. The analysis reveals how the characters' relationships influence their use of these strategies, demonstrating how these strategies align with the main themes of novel’s text connection, power dynamics, personal growth and understanding. This study not only contributes to our knowledge of the subtle patterns of interaction in fictional conversation but also gives us understanding of how politeness strategies function in literary context and provides insights into how civility is portrayed in fiction.